Isolation and molecular characterization of enterococci from different animal species - BATHINI, JAGRUTI; ARORA, A K; RAI, T S (The Indian Journal of Animal Sciences, 2018)
The study was undertaken to determine the occurrence of Enterococcus spp. with special reference to vancomycin resistant enterococci (VRE) in bovines, equines and poultry; detection of vancomycin resistance gene markers by polymerase chain reaction (PCR) and to compare VRE isolates by means of pulse field gel electrophoresis (PFGE). In this study, 60 VRE were isolated from 150 faecal samples. Besides vancomycin sensitivity, isolates were also tested for 6 more antimicrobial drugs by MIC. Significant number of isolates exhibited intermediate level of resistance to vancomycin (70%), norfloxacin (50%) and cephalothin (43.3%). Multidrug resistance (MDR) was observed in 37 (61.6%) isolates. Multiplex PCR revealed vanC1 (14), vanC2/3 (9), van C1 + vanC2/3 (11) but no vanA or vanB genes. Further genotyping of the VRE isolates carrying vanC genes using pulse field gel electrophoresis revealed 73% homology.